2003
DOI: 10.1080/10473289.2003.10466166
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Volatile Hydrocarbons in Urban Street Canyons

Abstract: Volatile hydrocarbons (VHCs) were monitored in two urban street canyons for 16 days. Measurements of 15 selected VHCs were performed simultaneously at three different sampling heights: at street level (2 m), at 8 m, and at the rooftop (25 m above the ground). The aim of the study was to investigate the factors responsible for the horizontal and vertical changes in VHC concentrations. Physical parameters controlling the concentration gradients (wind flow and speed) were enabled. It was concluded that dilution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[29] In a recent and more detailed study for urban streets, it was found that dilution and dispersion decrease the pollutant concentrations emitted at street level by approximately a factor of 6 between rooftop and street levels while low wind speeds were identified as the worst dispersion conditions. [21] Similarly, for urban parks, an early study showed that the plant density and structure provide an intensive decline in pollutant levels in the central area of the parks. [30] In another study, it was found that pollutant levels are greater at the peripheral than the central zones of the parks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] In a recent and more detailed study for urban streets, it was found that dilution and dispersion decrease the pollutant concentrations emitted at street level by approximately a factor of 6 between rooftop and street levels while low wind speeds were identified as the worst dispersion conditions. [21] Similarly, for urban parks, an early study showed that the plant density and structure provide an intensive decline in pollutant levels in the central area of the parks. [30] In another study, it was found that pollutant levels are greater at the peripheral than the central zones of the parks.…”
Section: Resultsmentioning
confidence: 99%
“…typical streets in Jerusalem have an aspect ratio of 0.5, [20] while aspect ratios for typical Athens streets may range from 1.2 to 4.2. [21] The selected sites are representatives of the Athens urban microenvironment; they have a variety of urban topography-geometry configurations and include parks, public squares with and without green areas and 'canyon' streets with trees. Measurements carried out and samples were collected from totally 28 different locations: 5 locations in two different parks, 14 locations in street canyons, and 9 locations in public squares (3 with areas of 1.0 ha, 3 with areas of 5.0 ha and 3 with areas of 10.0 ha).…”
Section: Study Areamentioning
confidence: 99%
“…Extensive research has been launched in recent years to study the pollutants dispersion in street canyons and recently a study has been published for VOCs dispersion in an Athens street canyon (Bakeas and Siskos 2003). In this study, inter-correlations of VOCs (r 2 ) were found to change with height of the sampling point in the street canyons.…”
Section: Case Studies Of Atmospheric Processes In the Urban Air Of Atmentioning
confidence: 95%
“…3 Percentages of estimated photochemical production of carbonyls during a summer-day (a) and a winter-day (b). Source: Bakeas et al 2003Environ Chem Lett (2008 orders of magnitude from those of acetaldehyde and three orders of magnitude from those of ozone.…”
Section: Case Studies Of Atmospheric Processes In the Urban Air Of Atmentioning
confidence: 99%
See 1 more Smart Citation